Time-Restricted Ketogenic Diet in Huntington's Disease: A Case Study - Phillips, Matthew C. L.; McManus, Eileen J.; Brinkhuis, Martijn; Romero-Ferrando, Beatriz (Frontiers in Behavioral Neuroscience, 2022)
Huntington’s disease (HD) is a progressive, fatal neurodegenerative disorder with limited treatment options. Substantial evidence implicates mitochondria dysfunction in brain and skeletal muscle in the pathogenesis of HD. Metabolic strategies, such as fasting and ketogenic diets, theoretically enhance brain and muscle metabolism and mitochondria function, which may improve the clinical symptoms of HD. We report the case of a 41-year-old man with progressive, deteriorating HD who pursued a time-restricted ketogenic diet (TRKD) for 48 weeks. Improvements were measured in his motor symptoms (52% improvement from baseline), activities of daily living (28% improvement), composite Unified HD Rating Scale (cUHDRS) score (20% improvement), HD-related behaviour problems (apathy, disorientation, anger, and irritability improved by 50-100%), and mood-related quality of life (25% improvement). Cognition did not improve. Weight remained stable and there were no significant adverse effects. This case study is unique in that a patient with progressive, deteriorating HD was managed with a TRKD, with subsequent improvements in his motor symptoms, activities of daily living, cUHDRS score, most major HD-related behaviour problems, and quality of life. Our patient remains dedicated to his TRKD, which continues to provide benefit for him and his family.